2020
DOI: 10.1002/art.41456
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in Patients With Inflammatory Arthritis: A Prospective Study on the Effects of Comorbidities and Disease‐Modifying Antirheumatic Drugs on Clinical Outcomes

Abstract: Objective To characterize the hospitalization and death rates among patients with inflammatory arthritis (IA) affected by coronavirus disease 2019 (COVID‐19) and to analyze the associations of comorbidities and immunomodulatory medications with infection outcomes. Methods Data on clinical and demographic features, maintenance treatment, disease course, and outcomes in individuals with IA (rheumatoid arthritis and spondyloarthritis) with symptomatic COVID‐19 infection were prospectively assessed via web‐based q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
114
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 34 publications
18
114
1
5
Order By: Relevance
“…2,[152][153][154] Multiple studies to date have reported significantly increased risk of serious infections in patients on sGC, with doses as low as 10 mg prednisone-equivalent, although this mostly corresponds to bacterial infections. 28,[155][156][157][158][159][160] Hydroxychloroquine (HCQ) use is recommended in most patients with SLE, owing to multiple health benefits in patients with SLE and overall safety. [161][162][163][164] Various observational studies have indicated a protective effect of HCQ against serious infections in SLE.…”
Section: Commonly Used Drugs In Sle and Predisposition To Viral Infecmentioning
confidence: 99%
“…2,[152][153][154] Multiple studies to date have reported significantly increased risk of serious infections in patients on sGC, with doses as low as 10 mg prednisone-equivalent, although this mostly corresponds to bacterial infections. 28,[155][156][157][158][159][160] Hydroxychloroquine (HCQ) use is recommended in most patients with SLE, owing to multiple health benefits in patients with SLE and overall safety. [161][162][163][164] Various observational studies have indicated a protective effect of HCQ against serious infections in SLE.…”
Section: Commonly Used Drugs In Sle and Predisposition To Viral Infecmentioning
confidence: 99%
“…There is a concern that patients undergoing immunosuppressive therapy for inflammatory rheumatic and musculoskeletal diseases (iRMD) could be more vulnerable to SARS-CoV-2 infection and hospitalisation than the general population, particularly in those patients with comorbidities such as diabetes, chronic obstructive pulmonary disease, and renal failure. 6 7 Several recent studies in patients with iRMD [8][9][10] and inflammatory bowel diseases (IBD) 11 suggested an increased risk for hospitalisation and severe disease when using glucocorticoids, although no effect on severity or mortality was found with biological diseasemodifying anti-rheumatic drug (DMARD) use. A decreased risk for severe was suggested in such populations with respect to anti-tumour necrosis factor alpha (TNFα) drugs.…”
Section: Autoinflammatory Disordersmentioning
confidence: 99%
“…Epidemiology use, although not with biologic or targeted synthetic diseasemodifying antirheumatic drugs (DMARDs). [8][9][10] During the initial crisis phase of the pandemic in Boston, Massachusetts (March and April 2020), we performed a comparative cohort study that demonstrated similar odds of hospitalisation and death but threefold higher odds of mechanical ventilation among patients with rheumatic disease versus 104 matched comparators without the rheumatic disease. 11 In this follow-up study, we examine COVID-19 outcomes and temporal trends in an expanded number of systematically identified patients with rheumatic disease and matched comparators 6 months into the ongoing COVID-19 pandemic.…”
Section: What Does This Study Add?mentioning
confidence: 99%